The Effect of Health Education With Animated Video Media on Bullying Knowledge in Adolescents at SMP Negeri 21 Palembang - Anggun Risma Dewi; Ayu Dekawaty; Suzanna Suzanna (Excellent Health Journal, 2025)
Adolescence or often called adolescence is a transition period from childhood to adulthood which is marked by physical, mental, emotional, social and moral development. One of the most common problems in adolescents is bullying. The negative impact of bullying is that both the perpetrator and the victim of bullying will experience disorders including low psychological well-being where the victim will feel uncomfortable, afraid, low self-esteem, and poor social adjustment, withdrawing from socializing, declining academic achievement, and even wanting to commit suicide. One strategy to improve adolescents' attitudes and knowledge about bullying is through health education through animated video media. This study aims to determine the effect of health education with animated video media on bullying knowledge in junior high school adolescents. This study is a quantitative study with a pre-experimental design using a one group pretest and posttest approach. The sampling technique is total sampling, with a total of 108 respondents. Data analysis using the Wilcoxon test. The average value of knowledge before the intervention was 75.09 and after the intervention was 20.85 with P Values ​​0.000 ≤ 0.05. There is an influence of animated video media on the average value of knowledge before and after being given health education about bullying knowledge in junior high school teenagers. It is hoped that schools can utilize animated video media to reduce bullying incidents in schools.